Quality of life in epilepsy - Singh, Prem; Pandey, Achyut Kumar (International Journal of Research in Medical Sciences, 2017)
Background: The quality of life (QOL) evaluation is a relatively new measure to evaluate the outcome of epilepsy. Many factors influence the quality of life of people with epilepsy, including seizure severity, stigma, fear, and the presence of cognitive or psychiatric problems. QOL is influenced by biological factors as well as cultural, social and religious beliefs and values. This study was planned to find out the impact of epilepsy on quality of life of epileptic patients. Methods: The study was conducted in the epilepsy clinic of department of neurology at a tertiary care hospital over a period of one year.101 patients were included after fulfilling the inclusion criteria. All the patients seeking treatment in the OPD were screened, assessed and then all procedures were fully explained to them. History regarding name, age sex, socio-demographic profile and detailed history regarding seizure disorder was taken from both the patient and the reliable informant. Bengali version of QOLIE-9 was used to assess the quality of life. Results: One hundred and one patients with epilepsy consisting of 70 men (69.3%) and 31 women (30.7%) were included. Their ages ranged from 15 to 52, the mean age being 26.17 (SD = 7.84). Out of the 101 patients, 65 patients (64.4%) were suffering from partial epilepsies and 36 patients (35.6%) were suffering from generalized epilepsies. Mean QOLIE-9 total scores were 16.66, 19.74, 20.13 and 24.00 in married, widows, unmarried and separated individuals respectively. The differences in the means were statistically significant on ANOVA (p value 0.002). Mean QOLIE-9 total scores were 27.75, 19.64, 19.65, 18.14 and 18.00 in primary, secondary, higher secondary, graduate and postgraduate individuals respectively. The differences were highly significant statistically on ANOVA (p value<0.001). Frequency of seizures per month was positively correlated with QOLIE-9 total scores (Pearson Correlation 0.622) and was highly statistically significant (p value<0.001). Conclusions: Frequent seizures, lower education level and single status are associated with lower quality of life in persons with epilepsy.